FORWARD, FUTURE AND OPTIONS ON STOCK EXCHANGE MARKET - Stošić Mihajlović, Ljiljana (Journal of process management and new technologies, 2016)
The main motive of the formation and use of forward contracts and futures, and options, was certainly profit. Making financial markets more efficient, in terms of expanding the range of available financial instruments and reduction in transaction costs, these financial innovations are beneficial for both investors and managers company. Primary purpose of derivatives such as forwards, futures and options is to enable control risks by investitures and primarily from inadequate price trends for all types of assets that could be subject to transactions in financial markets.